Changes in Noninvasive Liver Fibrosis Indices and Spleen Size During Chemotherapy: Potential Markers for Oxaliplatin-Induced Sinusoidal Obstruction Syndrome. Issue 2 (January 2016) - Park, Sehhoon; Kim, Hwi Young; Kim, Haeryoung; Park, Jin Hyun; Kim, Jung Ho; Kim, Ki Hwan; Kim, Won; Choi, In Sil; Jung, Yong Jin; Kim, Jin-Soo
Abstract : Abstract: Oxaliplatin-based regimens are standard treatments for the patients with colorectal cancer (CRC) and advanced gastric cancer (AGC). However, owing to hepatic sinusoidal obstruction syndrome (SOS), the use of oxaliplatin sometimes results in splenomegaly. The aim of the present study was to evaluate the correlation between chemotherapy-associated changes of noninvasive liver fibrosis indices and volumetric changes of the spleen. From February 2004 to April 2014, patients with CRC or AGC receiving oxaliplatin-based chemotherapy were studied. The possibility of SOS development was evaluated before and after the oxaliplatin exposure with splenic volume index (SVI). Four different noninvasive liver fibrosis indices were used for risk analysis, namely age-platelet index (API), AST-to-platelet ratio index (APRI), platelet-to-spleen ratio (PSR), and fibrosis-4 score (FIB-4). A total of 275 patients were eligible for evaluation: 200 patients had CRC and 75 patients had AGC. Using the cutoff of SVI increase ≥ 0.3, 113 patients (41.1%) were positive for splenomegaly. The changes of indices significantly correlated with SVI increase. Adjusted odds ratios for those indices were as follows: API = 1.16 (95% confidential interval [CI], 1.01–1.32; P  = .03); APRI = 2.45 (95% CI, 1.30–4.63; P  = .01); PSR = 0.69 (95% CI, 0.59–0.80; P  < .01); and FIB-4 = 1.37 (95% CI, 1.16–1.63; P  < .01). Optimal cutoff values with statistical significance were calculated and suggested. The changes of noninvasive liver fibrosis indices showed a good correlation with the increase in the spleen volume during oxaliplatin-based chemotherapy. Validation of these indices for monitoring of oxaliplatin-induced hepatic SOS is warranted. Abstract : Supplemental Digital Content is available in the text